Environmental factors of diarrhea prevalence among under five children in rural area of North Gondar zone, Ethiopia - Atalay Getachew; Alebachew Tadie; Mulat G.Hiwot; Tadesse Guadu; Daniel Haile; Teklay G.Cherkos; Zemichael Gizaw; Marta Alemayehu (BMC, 2018)
Abstract Background In the sub-Saharan countries, many of the children including found in health facilities are not having sufficient care of diarrhea. Diarrheal disease in these countries is one of the main causes of deaths for under-five children. Methods A community-based cross-sectional study design was used to collect data from May-June, 2016 to determine environmental factors of diarrhea prevalence among under five children in North Gondar Zone. Structured interview questionnaire and observational checklist were used to collect data. Using probability proportion to size, number of households was determined in each district. The multivariable binary logistic regression analysis with a 95% confidence interval and p < 0.05.was used to identify environmental factors associated with childhood diarrheal disease. Results Of the total 736 individuals surveyed from 736 households, a total of 163 (22.1%) with [95% CI (19.1-25.1)] under -five children had 2 week period diarrhea prevalence. Roof material [AOR: 1.99, 95% CI (1.1-3.82)], hand washing facility [AOR: 0.52, 95%CI (0.33-0.82)], presence of Latrine facility [AOR: 1.65, 95% CI (1.01-2.72)], presence of feces around the pit hole [AOR: 1.65, 95% CI (1.01-2.72)], presence of feces around the house compound [AOR: 1.65, 95% CI (1.01-2.72)] and risk of contamination of household storage had significant associations with diarrheal morbidity. Conclusion The prevalence of childhood diarrheal disease among under - five children in rural settings of northwest Ethiopia was high. Type of roof material, hand washing facility, presence of Latrine facility, presence of feces around the pit hole, presence of feces around the house compound and risk of contamination of household storage had significant associations with diarrheal morbidity.